PENGARUH KOMPENSASI TERHADAP KINERJA PERUSAHAAN PADA PT. BERLIAN JASA TERMINAL INDONESIA CABANG KUPANG - GASIM; TEDDY DOSIAS SENTINUWO; AKBAR YUSUF (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
To improve performance, companies have to deal with several ways: by providing adequatecompensation in accordance with the contribution of the company and a quality of life as well as aconducive work environment to create. This study aimed to determine the effect of the financialcompensation and non-financial compensation performance of the company PT. Berlian Jasa TerminalIndonesia Branch Kupang, the influence of financial and non-financial compensation simultaneously onthe performance of PT. Berlian Jasa Terminal Indonesia Branch Kupang. The sample is in this study was64 respondents were distributed to employees of PT. Berlian Jasa Terminal Indonesia Branch Kupang.Data analysis method is used, the quantitative analysis and use of analytical tools SmartPLS3. The resultsof the study for financial compensation positive and significant impact on the performance of PT. BerlianJasa Terminal Indonesia Branch Kupang, non-monetary compensation is also positive and significantimpact on the performance of PT. Berlian Jasa Terminal Indonesia Branch Kupang, financial and nonfinancialcompensation simultaneously positive and significant impact on the performance of PT. BerlianJasa Terminal Indonesia Branch Kupang.